What is the threshold for structural transformation that can reduce income inequality in sub-Saharan Africa? - ATANGANA, Siméon Serge; Nguenda Anya , Saturnin Bertrand (Journal of Income Distribution®, 2023)
The main objective of this paper is to study the threshold effect of structural transformation on income inequality in SSA. Our analysis sample consists of 18 countries, over a period from 1996-2015. Using a recently developed PSTR (Panel Smooth Treshold Regression) model, we determine the threshold endogenously. Thus, the Gini index is used as the explained variable and we use two indicators of structural transformation, intra-industry productivity and inter- industry productivity as the threshold variable. For the intra-industry productivity indicator the results indicate that there are at least two thresholds at which intra-industry productivity reduces income inequality in SSA. The use of structural change as a threshold parameter results in the existence of a single threshold of 22%, at which structural change starts to reduce income inequality in SSA. This confirms Kuznets' predictions about the distribution of income in the long run.